Level of understanding of Alzheimer disease among caregivers and the general population - Jorge, C.; Cetó, M.; Arias, A.; Blasco, E.; Gil, M.P.; López, R.; Dakterzada, F.; Purroy, F.; Piñol-Ripoll, G. (Neurología (Barcelona, English ed. ), 2021)
Understanding of Alzheimer disease (AD) is fundamental for early diagnosis and to reduce caregiver burden. The objective of this study is to evaluate the degree of understanding of AD among informal caregivers and different segments of the general population through the Alzheimer’s Disease Knowledge Scale (ADKS). We assessed the knowledge of caregivers in different follow-up periods (less than one year, between 1 and 5 years, and over 5 years since diagnosis) and individuals from the general population. ADKS scores were grouped into different items: life impact, risk factors, symptoms, diagnosis, treatment, disease progression, and caregiving. A total of 419 people (215 caregivers and 204 individuals from the general population) were included in the study. No significant differences were found between groups for overall ADKS score (19.1 vs 18.8, P = .9). There is a scarce knowledge of disease risk factors (49.3%) or the care needed (51.2%), while symptoms (78.6%) and course of the disease (77.2%) were the best understood aspects. Older caregiver age was correlated with worse ADKS scores overall and for life impact, symptoms, treatment, and disease progression (P < .05). Time since diagnosis improved caregivers’ knowledge of AD symptoms (P = .00) and diagnosis (P = .05). Assessing the degree of understanding of AD is essential to the development of health education strategies both in the general population and among caregivers. El conocimiento de la enfermedad de Alzheimer (EA) es fundamental para el diagnóstico precoz y para reducir la sobrecarga del cuidador. El objetivo fue evaluar el grado de conocimiento de la EA mediante la Alzheimer’s Disease Knowledge Scale (ADKS) en cuidadores informales y diferentes segmentos de población. Se evaluó el conocimiento a cuidadores en diferente periodo de seguimiento (menor de 1 año, entre 1-5 y más de 5 años desde el diagnóstico) y sujetos de la población general (PG). La puntuación ADKS se agrupó en distintos ítems: impacto vital, factores de riesgo, síntomas, diagnóstico, tratamiento, progresión de la enfermedad y cuidadores. Total de 419 personas; 215 cuidadores, 204 PG. Respecto a la puntuación global de la escala no se encontraron diferencias entre ambos grupos (19.1 vs 18.8; p = 0.9). Destaca un escaso conocimiento de los factores de riesgo de la enfermedad (49.3%) y de los cuidados necesarios (51.2%) mientras que los síntomas (78.6%) y el curso de la enfermedad (77.2%) fueron los aspectos mejor reconocidos. Entre las variables, la edad del cuidador se correlacionó con peor puntuación total de la escala ADKS, peor conocimiento sobre el impacto vital, síntomas, cuidados y de la progresión de la enfermedad (p < 0.05). La duración de los cuidadores mejoró el conocimiento de los síntomas (p = 0.00) y el diagnóstico de la enfermedad (p = 0.05). Evaluar el grado de conocimiento de la enfermedad es fundamental para poder elaborar estrategias de educación sanitaria tanto a nivel poblacional como en los cuidadores.